2009
DOI: 10.1007/s10126-009-9179-0
|View full text |Cite
|
Sign up to set email alerts
|

Highly Unsaturated Fatty Acid Synthesis in Atlantic Salmon: Characterization of ELOVL5- and ELOVL2-like Elongases

Abstract: Running title: Characterisation of salmon ELOVL5-and ELOVL2 elongases Abbreviations: aa, amino acid; ARA, arachidonic acid (20:4n-6); DHA, docosahexaenoic acid (22:6n-3); EPA, eicosapentaenoic acid (20:5n-3); ER, endoplasmic reticulum; FA, fatty acid; FO, fish oil; HUFA, highly unsaturated fatty acids (carbon chain length ≥ C 20 with ≥ 3 double bonds); LO, linseed oil; ORF, open reading frame; PUFA, polyunsaturated fatty acids; Q-PCR, quantitative (real-time) polymerase chain reaction; RACE, rapid amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
226
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(259 citation statements)
references
References 41 publications
28
226
2
3
Order By: Relevance
“…Elovl4 proteins are highly conserved through evolution (Leonard et al, 2004). Consistent with that, the phylogenetic analysis revealed that the salmon elovl4 cDNA encodes a protein more similar to other Elovl4 orthologues from mammals, birds and fish, than the other Elovl family proteins characterised previously in Atlantic salmon, the Elovl5_a and Elovl5_b, and Elovl2 Morais et al, 2009 nigroviridis and Atlantic salmon Elovl4. This clustering pattern is consistent with the differing functional activities between the two fish Elovl4 groups.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Elovl4 proteins are highly conserved through evolution (Leonard et al, 2004). Consistent with that, the phylogenetic analysis revealed that the salmon elovl4 cDNA encodes a protein more similar to other Elovl4 orthologues from mammals, birds and fish, than the other Elovl family proteins characterised previously in Atlantic salmon, the Elovl5_a and Elovl5_b, and Elovl2 Morais et al, 2009 nigroviridis and Atlantic salmon Elovl4. This clustering pattern is consistent with the differing functional activities between the two fish Elovl4 groups.…”
Section: Discussionsupporting
confidence: 72%
“…showing high elongation efficiency towards C18 and C20 PUFA, whereas Elovl2 produced C24 PUFA from C20 and C22 PUFA and, in all cases, the production of longer PUFA was negligible Morais et al, 2009). Interestingly, a recent study has shown that mice ELOVL2 participates in the biosynthesis of n-6 VLC-PUFA that are critical in male fertility, and that 24:5n-6 appears a preferred substrate for murine ELOVL2 (Zadravec et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unfortunately, we did not have the standards in order to establish whether this was paralleled by a positive effect on the content of c24:5 n-3 and c24:4 n-6 as well. Fatty acid-dependent changes in hepatic ELOVL2 expression have also been reported in rat and salmon (Igarashi et al, 2007a;Morais et al, 2009).…”
Section: Discussionmentioning
confidence: 63%
“…Research investigating the Fad and Elovl gene families that desaturate and elongate LC‐PUFAs has largely been restricted to bilaterian taxa (Carmona‐Antoñanzas et al., 2011; Castro et al., 2012; Fonseca‐Madrigal et al., 2014; Kabeya et al., 2017; Li et al., 2017; Li et al., 2010; Mohd‐Yusof et al., 2010; Monroig, Guinot, et al., 2012; Monroig, Navarro, et al., 2012; Monroig, Webb, et al., 2011; Monroig et al., 2010, 2016, 2017, 2013; Morais et al., 2009; Surm et al., 2015). We have investigated the phylogenetic and molecular evolutionary histories of the Fad and Elovl gene families in phylum Cnidaria, to provide insights into evolution and the distribution of these gene families in Metazoa outside of bilaterian taxa.…”
Section: Discussionmentioning
confidence: 99%